UN ENFOQUE ESTRATÉGICO PARA LA GESTIÓN DEL CONOCIMIENTO EN LA UNIVERSIDAD. LA EXPERIENCIA DE LA UNIVERSIDAD PERUANA DE CIENCIAS APLICADAS (UPC) - Morgan Rozas, Milagros (2006)
In the current age, University has a leading role in the impulse of making a society of information become a society of knowledge. To confront this task, Peruvian University of Applied Sciences (UPC) considers necessarily to manage and to value the academic contents produced by its teachers and researchers, since it recognizes that sharing the above mentioned contents is an important mechanism to create and spread the knowledge. The implementation of DELFOS (2005), the Agent of Digital Contents of the UPC, reflects an effort for improving the knowledge management by means of the integration of technologies. In the same way the above mentioned implementation turns out to be important due to the fact that it witness a cultural change in the organization, in which teachers and students are learning to create and to share the knowledge. The present work, therefore, proposes an analysis of the experience on knowledge management of the UPC from three different angles: organizational, technological and pedagogical.